2006
DOI: 10.1136/jcp.2005.026393
|View full text |Cite
|
Sign up to set email alerts
|

Intrapatellar tendon lipoma with chondro-osseous differentiation: detection of HMGA2-LPP fusion gene transcript

Abstract: A 54 year old man developed an unusual lipoma in the patellar tendon, consisting of a fibro-adipose component and a chondro-osseous component. The fibro-adipose component contained mature adipocytes, lipoblasts, and fibroblasts; the chondro-osseous component showed typical endochondral bone formation. Molecular analysis showed that the identical HMGA2-LPP fusion transcript-characteristic of lipoma, parosteal lipoma, and pulmonary chondroid hamartoma-was detectable in the both components.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
10
0
4

Year Published

2008
2008
2015
2015

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 11 publications
(14 citation statements)
references
References 12 publications
0
10
0
4
Order By: Relevance
“…Currently, the terms osteolipoma and ossifying lipoma are generally used synonymously for soft tissue tumors without relationship to the underlying bone, while ossifying parosteal lipoma is used if the tumor is intimately associated with the periosteum. A review of the English literature found that, outside the head and neck area, lipomas with osseous differentiation have been reported in deep locations adjacent to bone tissue in the thigh [10][11][12][13], knee [14,15], sternoclavicular region [16], shoulder [17], wrist [14], hand [18], intraspinal [19] or in superficial subcutaneous tissue [20,21]. More than 60 % of the cases occur in the head and neck region, where they have been described in intraspinal [22], intracranial [23] (suprasellar/hypothalamic and interhemispheric) and extracranial-extraspinal locations [3][4][5][6][24][25][26][27][28][29][30][31][32][33][34][35][36][37][38][39][40][41][42].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Currently, the terms osteolipoma and ossifying lipoma are generally used synonymously for soft tissue tumors without relationship to the underlying bone, while ossifying parosteal lipoma is used if the tumor is intimately associated with the periosteum. A review of the English literature found that, outside the head and neck area, lipomas with osseous differentiation have been reported in deep locations adjacent to bone tissue in the thigh [10][11][12][13], knee [14,15], sternoclavicular region [16], shoulder [17], wrist [14], hand [18], intraspinal [19] or in superficial subcutaneous tissue [20,21]. More than 60 % of the cases occur in the head and neck region, where they have been described in intraspinal [22], intracranial [23] (suprasellar/hypothalamic and interhemispheric) and extracranial-extraspinal locations [3][4][5][6][24][25][26][27][28][29][30][31][32][33][34][35][36][37][38][39][40][41][42].…”
Section: Discussionmentioning
confidence: 99%
“…These tumors may originate directly from a multidirectional differentiation capacity of adipose tissue-derived stem cells [10,14,20], or they may arise from secondary metaplasia of fibroblasts after repetitive trauma, metabolic changes, or ischemia [14,52]. The few cytogenetic studies on osteolipomas and parosteal lipomas show they share the same t(3;12) translocations as conventional soft tissue lipomas [14,15,53,54]. Matsui et al detected an identical HMGA2-LPP fusion transcript in both the fibro-adipose and the chondro-osseous components of a tendon lipoma, suggesting that the HMGA2-LPP fusion protein induces fibroadipogenesis as well as osteochondrogenesis [15].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…[23,24] Fusion of the HMGA2 gene with other genes resulting in increased HMGA2 activity has been noted in lipoma [25,26], pulmonary chondroid hamartoma [23], and uterine leiomyoma [23,24] among other neoplasms. Aberrant HMGA2 expression has been identified in benign mesenchymal tumors, including lipoma [27][28][29], uterine leiomyoma [30], inflammatory myofibroblastic tumor [31], and chondroma [32], and in malignant tumors, including well differentiated liposarcoma [33], uterine leiomyosarcoma [34], osteosarcoma [35] and acute lymphoblastic leukemia [36].…”
Section: Discussionmentioning
confidence: 99%
“…An image, however, with infiltration of the neighbouring tissues raises suspicion of a liposarcomas. X-rays and CT scans are useful in the rare cases of tumour calcifications or ossifications, as MRIs frequently fail to detect them [9,14,18]. The histological identification of the tumour through biopsy is regarded by many researchers as necessary only in cases where no diagnosis is achieved through the MRI.…”
Section: Discussionmentioning
confidence: 99%